Field hockey injuries and personal protective equipment: a status survey of German national teams - Gorks, S.; Henke, T.; Platen, P. (British Journal of Sports Medicine, 2021)
Background In order to prevent sports injuries, it is necessary to know the number of injuries and injury mechanisms of sports-related injuries. In addition, acceptance and use of personal protective equipment (PPE) should be examined. The results give a better overview in German elite hockey.